Optimal time-consistent government debt maturity - Davide Debortoli; Ricardo Nunes; Pierre Yared (Federal Reserve Bank of Boston, 2016)
This paper develops a model of optimal debt maturity in which the government cannot issue statecontingent debt. As the literature has established, if the government can perfectly commit to fiscal policy, it fully insulates the economy against government spending shocks by purchasing short-term assets and issuing long-term debt. These positions are quantitatively very large relative to GDP and do not need to be actively managed by the government. Our main result is that these conclusions are not robust when lack of commitment is introduced. Under lack of commitment, large and tilted debt positions are very expensive to finance ex-ante since they ex-post exacerbate the government's problem stemming from a lack of commitment. In contrast, a flat maturity structure minimizes the cost entailed by a lack of commitment, though this structure also limits the ability to insure against shocks and increases the volatility of fiscal policy distortions. We show that the optimal time-consistent maturity structure is nearly flat because reducing average borrowing costs is quantitatively more important for welfare than reducing fiscal policy volatility. Thus, under lack of commitment, the government actively manages its debt positions and can approximate optimal policy by confining its debt instruments to consols.
Keywords: H63; H21; E62; 330; public debt; optimal taxation; fiscal policy